Comparison of hepatic arterial infusion chemotherapy with mFOLFOX vs. first-line systemic chemotherapy in patients with unresectable intrahepatic cholangiocarcinoma - Zhenyun Yang; Zhenyun Yang; Yizhen Fu; Yizhen Fu; Weijie Wu; Weijie Wu; Zili Hu; Zili Hu; Yangxun Pan; Yangxun Pan; Juncheng Wang; Juncheng Wang; et al. (Frontiers in Pharmacology, 2023)
Background: Systemic chemotherapy (SC) remains the only first-line treatment for unresectable intrahepatic cholangiocarcinoma (iCCA). Hepatic arterial infusion chemotherapy (HAIC) has been recently proven to be effective in managing hepatocellular carcinoma (HCC). Hence, our study aims to investigate the safety and efficacy of HAIC in treating unresectable iCCA patients.Methods: We reviewed 146 patients with unresectable iCCA who had received HAIC or SC between March 2016 and March 2022 in a retrospective manner. Outcomes of patients and safety were compared between the HAIC and SC groups.Results: There were 75 and 71 patients in the HAIC and SC groups, respectively. The median OS in the HAIC and SC groups was 18.0 and 17.8 months (p = 0.84), respectively. The median PFS in the HAIC and SC groups was 10.8 and 11.4 months (p = 0.59), respectively. However, the HAIC group had significantly longer intrahepatic progression-free survival (IPFS) than the SC group (p = 0.035). The median IPFS in the HAIC and SC groups was 13.7 and 11.4 months, respectively. According to the OS (p = 0.047) and PFS (p = 0.009), single-tumor patients in the HAIC group appeared to benefit more. In addition, the overall incidence of adverse events (AEs) was lower in the HAIC group than that in the SC group.Conclusion: Our study revealed that HAIC was a safe and effective therapeutic regimen for unresectable iCCA with better intrahepatic tumor control when compared to SC. Meanwhile, patients with single tumor were more likely to benefit from HAIC than SC.